4(3x + 2) + 3(2x +3) - 28 = 7(2x + 5) + 6
|2x + 7| = 9
4x - 5y = 25 si |x| < 12
Răspunsuri la întrebare
Răspuns de
0
1) 4(3x+2) +3(2x+3) -28= 7(2x+5) +6=
12x + 8+6x+9-28=14x+35+6=
18x- 11=14x+41
18-14x=41+11
4x+52
x=52:4
x= 13
2) l2x+7l=9
2x+7=+-√9
2x+7∈{+3;-3}/-7
2x∈{-4;-10}/-2
x∈{-6;-12}
12x + 8+6x+9-28=14x+35+6=
18x- 11=14x+41
18-14x=41+11
4x+52
x=52:4
x= 13
2) l2x+7l=9
2x+7=+-√9
2x+7∈{+3;-3}/-7
2x∈{-4;-10}/-2
x∈{-6;-12}
Alte întrebări interesante
Engleza,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă